Interaction of Bephratelloides cubensis (Hymenoptera: Eurytomidae) with Annona macroprophyllata fruits in orchards of Chiapas, Mexico - González-Sánchez, José Norman; González-Esquinca, Alma Rosa; Durán-Ruiz, Claudia Azucena; De-La-Cruz-Chacón, Iván; Castro-Moreno, Marisol (Revista de Biología Tropical, 2021)
ABSTRACT. Introduction: Annona macroprophyllata Donn. Smith. (Annonaceae) (syn. Annona diversifolia Saff.) is a valued fruit tree species known as papausa. In Mexico and Central America, this fruit has become an important crop because of its tasty flavor and high pulp content. Its fruits are frequently damaged by the incidence of wasps of the genus Bephratelloides Girault (Hymenoptera: Eurytomidae), which develop inside the seeds. Objective: to report the interaction of Bephratelloides cubensis Ashmead during its life cycle in fruits of A. macroprophyllata. Methods: We periodically collected fruits in different states of growth recording a) oviposition, b) the moment of evident infection, c) the development of the wasps inside the seeds, and d) their emergence as adults. We also determined the proportion of damaged fruits and seeds. Results: The data indicate that wasps preferred to oviposit on fruits with a diameter of less than 8 cm, oviposition was more frequent between 11:00 am and 03:00 pm., and there was 26 % infestation of fruits, and 9 % of seeds. Conclusion: It is an obligatory interaction for the wasp, the highest proportion of attack on fruits was in the early stages of fruit development and control actions should focus on the protection of these early stages.